The Effect of Interpersonal Relationships on Job Satisfaction Through Organizational Culture at the Camat Office, Samalanga District, Bireuen Regency - Fatimah Zuhra (PT Inovasi Pratama Internasional, 2022)
The Samalanga sub-district office is one of the sub-district offices in Bireuen Regency, which is the operational activity needs competent workers, therefore the management of human resources should also be improved. In this case the interaction between superiors and subordinates and employees with employees must be well established. When the interpersonal relationship in the work environment has been applied so that in the company or agency will create an organizational culture that will differentiate the company with other companies. Habits are run continuously and accepted by every person in the company, this will affect the job satisfaction. The research that is used is a research model of a quantitative approach by collecting data in the form of numbers. The samples used are 64 respondents using a sampling technique that is a saturated sample. In this research, the researcher used the data analysis of validity test, reliability test, normality test, linearity test, and path analysis with the aim to know the direct effect and indirect effect between the variables of interpersonal relationship to job satisfaction through organizational culture. The research results show that Interpersonal Relationship has no direct effect to Job Satisfaction. While the Interpersonal Relationship has indirect effect to Job Satisfaction Through Organizational Culture. Interpersonal Relationships within the company will be well established when employees have been carrying out habits that will give personal satisfaction to employees in carrying out the duties and responsibilities.